The performance gut: a key to optimizing performance in high-level athletes: a systematic scoping review - Carlone, Junior; Parisi, Attilio; Fasano, Alessio (Frontiers in Sports and Active Living, 2025)
IntroductionThe gut microbiome represents a key ecosystem influencing athletic performance through energy metabolism modulation, inflammatory response regulation, and recovery optimization in high-level athletes. However, the relationship between performance and gut microbiome composition in high-level athletes remains poorly understood.ObjectivesThis systematic scoping review aims to map the current evidence on the relationship between training and gut microbiome in high-level athletes, identify specific patterns in microbial response to different training and sports, analyse the effects of nutritional interventions and highlight some methodological and knowledge gaps in the current literature.MethodologyFollowing the PRISMA-ScR framework, a systematic search was conducted on PubMed, Scopus and Web of Science (2015-2025). Studies were selected according to defined criteria, including a population of high-level athletes, interventions through training and/or nutritional protocols and based on outcomes related to performance and health.ResultsNineteen studies met the inclusion criteria, comprising 12 experimental studies and 7 systematic/narrative reviews. The analysis of the studies revealed possible sport-specific patterns in microbiome modulation, with distinctive alterations in metabolic profiles, significant correlations between microbial stability and athletic performance, synergistic effects between training and probiotic supplementation and significant impacts of nutritional strategies and hormonal contraceptives on microbiome composition. The heterogeneity in analysis methodologies and the limited duration of studies emerge as the main limitations of the present study.ConclusionsThe evidence suggests that the significant role of the gut microbiome in athletic performance optimization may be considered in the future, highlighting the importance of implementing an integrated approach between training and nutrition. Further studies are needed to define specific microbiome trends for different types of sports, competition levels and supplementation targeted at implementing performance outcomes in high-level athletes.Systematic Review Registrationhttps://osf.io/yh49t, identifier YH49T.